2006
DOI: 10.1089/ars.2006.8.395
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Activates Defensive Genes and Protects Neurons Against Oxidative Stress

Abstract: Spices and herbs often contain active phenolic substances endowed with potent antioxidative properties. We had previously shown that curcumin, the yellow pigment in curry, strongly induced HO-1 expression and activity in rat astrocytes. In the CNS, HO-1 has been reported to operate as a fundamental defensive mechanism for neurons exposed to an oxidant challenge. Treatment of astrocytes with curcumin upregulated expression of HO-1 protein at both cytoplasmic and nuclear levels, as shown by immunofluorescence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(106 citation statements)
references
References 47 publications
4
101
0
1
Order By: Relevance
“…mg/kg) of curcumin were administered chronically, and the effects of curcumin were focused on the prevention of impaired hippocampal neurogenesis induced by chronic stress. Similarly, most previous in vivo studies of curcumin were focused on the ability of high doses of curcumin (5-200 mg/kg) to protect neurons against various types of stress (25,30,59). Interestingly, we found that a 40-fold higher dose of curcumin fails to increase the numbers of BrdU-positive cells and were not toxic to neural stem cells in adult hippocampus (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mg/kg) of curcumin were administered chronically, and the effects of curcumin were focused on the prevention of impaired hippocampal neurogenesis induced by chronic stress. Similarly, most previous in vivo studies of curcumin were focused on the ability of high doses of curcumin (5-200 mg/kg) to protect neurons against various types of stress (25,30,59). Interestingly, we found that a 40-fold higher dose of curcumin fails to increase the numbers of BrdU-positive cells and were not toxic to neural stem cells in adult hippocampus (supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, curcumin can activate the Nrf2-ARE and p38 MAP kinase pathways in tumor cells resulting in the induction of the expression of phase 2 enzymes such as heme oxygenase-1 (29). Studies of the effects of curcumin on neurons suggest that it can induce the expression of cytoprotective proteins such as heme oxygenase-1 (30). Emerging evidence suggests that some phytochemicals exert their health-promoting effects by activating one or more adaptive cellular stress response pathways (31).…”
Section: Neural Progenitor Cells (Npc)mentioning
confidence: 99%
“…Beneficial effects were also obtained using a mixture of curcuminoids that are commonly used as a nutritional supplement, particularly curcumin-95. The expression of HO-1 is increased in astrocytes treated with curcumin at 5-15 µM concentrations (51).…”
Section: Antioxidant Activitymentioning
confidence: 94%
“…Another mechanism is the activation of one or more adaptive cellular stress response signaling pathways by the phytochemical, which is the topic of this review. For example, exposure of neurons to sulforaphane (present in high amounts in broccoli), curcumin (an Indian spice from the turmeric root), or allicin (from garlic) can protect the neurons against a range of metabolic, chemical, and oxidative insults (Bautista et al, 2005;Scapagnini et al, 2006;Han et al, 2007). However, high concentrations of all of the latter phytochemicals can damage and kill neurons, demonstrating a typical biphasic hormesis-based dose-response curve.…”
Section: Hormesis and The Biphasic Dose Response To Phytochemicalsmentioning
confidence: 99%